Estimating Crack Effects on Electrical Characteristics of PV Modules Based on Monitoring Data and I-V Curves - Feng L.; Zhang J.; Kiong T.S.; Ding K.; Amin N.; Hamelmann F.U. (IEEE Electron Devices Society, 2024)
This study presents an approach to investigate microcrack effects on the output characteristics of photovoltaic (PV) modules based on a theoretical model that is derived from the equivalent single-diode model through monitoring data and current-voltage (I-V) curves. Meanwhile, an innovative parameter optimization algorithm based on particle swarm optimization is developed to extract the parameters. The parametric effects of microcracks on the electrical performance of PV modules are further explored under different meteorological conditions. It was found that the microcracks are formed early without creating inactive areas in solar cells, and the microcrack effects on the output performance of the PV modules are small. The temperature of the normally operating solar cells in a cracked PV module is lower than that of solar cells in a normal PV module. The number of equivalent mismatched solar cells caused by microcracks in the cracked PV module varies continuously with irradiance and temperature. Except for the apparently unaffected I0, microcracks not only greatly reduce the Iph and Rsh but also have a more serious negative impact on the Rs and n of the PV module at high irradiance. Meanwhile, the n-normal, Rs-normal, and Rsh-normal of the normal solar cells and the Rsh-cracks of the cracked solar cells in the cracked PV module are exponentially related to the irradiance. Finally, the experimental validation is effectively implemented to prove the great effectiveness and suitability of the proposed method. The average voltage error of each reconstructed I-V curve based on the extracted parameters and the average errors in Pm, Vm, Im, and Voc of the cracked PV module for 532 I-V curves are 1.15 V, 0.67%, 0.85%, 0.49%, and 0.089%, respectively. 2011-2012 IEEE.